2000
DOI: 10.1016/s1526-9523(99)00005-7
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Women'S Health Needs In Yemen: A Midwifery Perspective

Abstract: Maternal mortality in Yemen is one of the highest in the world. Reaching the rural majority of the population with primary health care services has been a continual priority for the nation. Despite efforts to expand health services, access to maternal and child health care remains low. The training of community midwives nationwide has been undertaken recently to address the need for maternal and child health services, particularly in rural areas. Several lessons have been gained through this initial training t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Given the gains in expanding EmONC services overall, the focus should shift to policies that reduce inequities and improve quality of care. Special strategies are warranted to address human resource constraints: geographic selection for pre-service training of specialists and midwives, remote area incentives, task shifting, public-private partnerships, and improving staff retention have been shown to be effective in other lowresource settings [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Given the gains in expanding EmONC services overall, the focus should shift to policies that reduce inequities and improve quality of care. Special strategies are warranted to address human resource constraints: geographic selection for pre-service training of specialists and midwives, remote area incentives, task shifting, public-private partnerships, and improving staff retention have been shown to be effective in other lowresource settings [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…22 A review of health care in Yemen in 2000 illustrates the cultural and geographic challenges in attempts to develop skilled health workers through task shifting. 23 In Yemen, untrained birth attendants have attended the majority of births in rural areas, and nomadic women commonly gave birth without assistance. A national curriculum began educating midwives in a 3-year program in 1997, and female primary health workers are trained in nursing and midwifery skills in a oneyear course.…”
Section: Challenges To Expansion Of Task Shifting In Low-resource Natmentioning
confidence: 99%
“…The majority of participants reported that they did not know the actual qualifications of health workers, which indicates that the results of the YFH survey of doctor led (20.1%) and midwife led (6.7%) deliveries (MoPHP, 2003) may not in fact provide true representation of professional community service provision. Also within Yemeni culture women are forbidden to travel unaccompanied by a male relative (Penney, 2000;EMRO, 2006) and consent from the husband must be provided for an operation to be conducted. It is also the cultural norm for husbands to be absent during labour and birth.…”
Section: ) Demographic Cultural and Political Factors In Yemenmentioning
confidence: 99%
“…Firstly, the political climate does not attract doctors to work in remote health centers of Yemen (Al Serouri et al, 2009;Hofmeyr et al, 2009), and secondly, cultural restrictions inhibit the majority of childbearing women from being attended upon by a male doctor (EMRO, 2006;Encyclopedia of the Nations, 2007;Penney, 2000). Due to the impoverished road infrastructure, transporting childbearing women to the closest hospital is an arduous task that can take as long as 4-6 hours (Penney, 2000). Few people own a car, with renting one expensive and the only means of transportation to the towns and cities (MoPHP, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation